Magnetic ground state of plutonium dioxide: DFT+U calculations - Hou, Yue-Fei; Jiang, Wei; Li, Shu-Jing; Fu, Zhen-Guo; Zhang, Ping (Chinese physics B, 2023)
The magnetic states of the strongly correlated system plutonium dioxide (PuO 2 ) are studied based on the density functional theory (DFT) plus Hubbard U (DFT+ U ) method with spin–orbit coupling (SOC) included. A series of typical magnetic structures including the multiple- k types are simulated and compared in the aspect of atomic structure and total energy. We test LDA, PBE, and SCAN exchange–correlation functionals on PuO 2 and a longitudinal 3 k antiferromagnetic (AFM) ground state is theoretically determined. This magnetic structure has been identified to be the most stable one by the former computational work using the hybrid functional. Our DFT+ U + SOC calculations for the longitudinal 3 k AFM ground state suggest a direct gap which is in good agreement with the experimental value. In addition, a genetic algorithm is employed and proved to be effective in predicting magnetic ground state of PuO 2 . Finally, a comparison between the results of two extensively used DFT+ U approaches to this system is made.